Mathematical pluralism - Priest, Graham 1948- (Cambridge elements. Elements in the philosophy of mathematics, 2024)
Mathematical pluralism is the view that there is an irreducible plurality of pure mathematical structures, each with their own internal logics; and that qua pure mathematical structures they are all equally legitimate. Mathematical pluralism is a relatively new position on the philosophical landscape. This Element provides an introduction to the position